Proton‐Coupled Reduction of the Catalytic [4Fe‐4S] Cluster in [FeFe]‐Hydrogenases. Issue 52 (30th November 2017) - Senger, Moritz; Laun, Konstantin; Wittkamp, Florian; Duan, Jifu; Haumann, Michael; Happe, Thomas; Winkler, Martin; Apfel, Ulf‐Peter; Stripp, Sven T.
Abstract: In nature, [FeFe]‐hydrogenases catalyze the uptake and release of molecular hydrogen (H2 ) at a unique iron‐sulfur cofactor. The absence of an electrochemical overpotential in the H2 release reaction makes [FeFe]‐hydrogenases a prime example of efficient biocatalysis. However, the molecular details of hydrogen turnover are not yet fully understood. Herein, we characterize the initial one‐electron reduction of [FeFe]‐hydrogenases by infrared spectroscopy and electrochemistry and present evidence for proton‐coupled electron transport during the formation of the reduced state Hred′. Charge compensation stabilizes the excess electron at the [4Fe‐4S] cluster and maintains a conservative configuration of the diiron site. The role of Hred′ in hydrogen turnover and possible implications on the catalytic mechanism are discussed. We propose that regulation of the electronic properties in the periphery of metal cofactors is key to orchestrating multielectron processes. Abstract : The molecular details of the hydrogen turnover by [FeFe]‐hydrolases in nature are not yet fully understood. FTIR spectro‐electrochemical studies on [FeFe]‐hydrogenases now prove there is a proton‐coupled electron transfer in the reduction of the catalytic [4Fe‐4S] cluster.